INCOME INEQUALITY IN DEVELOPING AND TRANSITION ECONOMIES IN ASIA: RECENT PATTERNS AND POLICY DRIVERS (2017–2024 YEARS EVIDENCE) - Muhammadkhon Muydinov (Modern American Journals, 2025)
Income inequality remains a central development constraint in Asia, especially for countries navigating structural transformation, urbanization, and institutional transition. This study compares recent inequality dynamics across a mixed group of transition economies (Uzbekistan, Kazakhstan) and developing/emerging economies (China, Viet Nam, Indonesia, Philippines, India, Bangladesh) using the World Bank’s Gini index and contextual macro indicators (GDP per capita, current US$). Results show (i) moderate inequality in Uzbekistan and Kazakhstan, but with recent widening in Uzbekistan (2022–2024); (ii) declining inequality in China since 2018; (iii) persistently higher inequality in the Philippines; and (iv) middle-range inequality in Viet Nam and Indonesia with short-term fluctuations. The findings support the view that inequality trajectories in Asia are shaped by the interaction of labor-market formality, fiscal redistribution capacity, spatial concentration of growth, and exposure to shocks. Policy implications emphasize targeted social protection, equalization transfers, human capital investment, and productivity-enhancing structural reforms to broaden the gains from growth.
Keywords: Income inequality, Gini index, transition economies, developing Asia, spatial inequality, inclusive growth.